PEMANFAATAN TEPUNG BEKATUL RENDAH LEMAK PADA PEMBUATAN KRIPIK SIMULASI - Evy Damayanthi; Dwi Inne Listyorini (Food and Nutrition Society of Indonesia, 2006)
The objectives of this study are to determine the substitution level of defatted rice bran flour substituted to wheat flour, to know the impact of defatted rice bran flour substitution to physical, chemical and organoleptic characteristics of simulated chips, and to compare defatted rice bran flour with whole rice bran flour as substituted raw material in making of simulated chips to physical, chemical, and organoleptic characteristics. The substitution of defatted rice bran increased content of water, ash, protein and fiber, but fat, carbohydrate and energy decreased compare with control simulated chips (a = 0.05). Organoleptic test of simulated chips with some levels of defatted rice bran flour substitution showed that acceptance of panelist to color has mode ranged from not like to like; mode of aroma ranged from neutral to like; and both of taste and crispiness has mode ranged from not like to like. Percentage of panelist that accepted simulated chips color in some level of defatted rice bran flour substitution ranged from 20% to 96.7%, aroma 76.7% to 90%, taste 50% to 100% and crispiness 53.3% to 100%. The substitution of defatted rice bran flour will decrease acceptance of panelist to color, aroma, taste and crispiness (a = 0,05). Simulated chips substituted by defatted rice bran flour and whole rice bran flour shows that the content of water, ashes, carbohydrate, energy, insoluble dietary fiber and total dietary fiber of simulated chips were not significantly difference (a = 0.05), but there was a significantly difference for fat and soluble dietary fiber. The organoleptic test showed that the color, aroma and taste of simulated chips were not significantly difference, but there was a significantly difference for crispiness (a = 0,05).